HUBUNGAN KUALITAS TIDUR DENGAN TEKANAN DARAH PADA MAHASISWA TINGKAT AKHIR PRODI S1 KEPERAWATANSTIKES BANYUWANGI TAHUN 2022 - Fany Anitarini; Lina Indah Sari; Achmad Efendi (STIKes Maharani Malang, 2022)
Introduction: The quality of sleep in final semester students is easily disturbed due to excessive physical activity, anxiety so that it can make sleep not fulfilled properly then it causes disturbances in several organs, one of which is an increase in blood pressure where if there is an increase in blood pressure then it will result in heart disease and stroke. The purpose of this study was to determine the relationship between sleep quality and blood pressure in final semester of undergraduate nursing students of Stikes Banyuwangi in 2022. Methods: This research was quantitative (analytic) with a cross sectional research design with a total sampling technique of 93 respondents. The instruments used for data collection were questionnaire sheets and observation sheets. The data were analyzed using SPSS 24 application with Chi-Square test. Result and analysis: The results showed that most of the sleep quality was in the poor category (59.1%) and most experienced normal blood pressure (62.4%). After statistical analysis, the p-value is 0.000, which means Ho is rejected and Ha is accepted, so it can be concluded that there is a relationship between sleep quality and blood pressure in students at the end of the undergraduate nursing study program, Stikes Banyuwangi in 2021. Discussion: Sleep quality in the final semester mostly experienced sleep quality as many as 55 respondents (59.1%). Blood pressure of the majority of experienced normal blood pressure, as many as 58 respondents (62.4%). Good sleep quality will result in normal blood pressure. So, it is hoped that students will rearrange their sleep patterns in order to get good sleep quality. Keyword: Sleep quality, Blood Pressure.